“The crime «tercería locativa». Of love, clandestine sex and prostitution, 1944-1973” - Madrid Cruz, María Dolores (Cuadernos de Historia del Derecho, 2024)
The crime ‘tercería locativa’ was created by the Penal Code of 1963 as a result of the European abolitionist movement in its fight against trafficking in women. The prosecution of those who provided rooms or premises for the practice of ‘illicit’ sexual acts was intended as an instrument against prostitution, but it also became a mechanism to control sexual practices during Franco's regime.
Keywords: tercería locativa; prostitution; clandestine sex; franquism; Supreme Cour; Jurisprudence